2012
DOI: 10.1371/journal.pbio.1001415
|View full text |Cite
|
Sign up to set email alerts
|

Loss of FGF-Dependent Mesoderm Identity and Rise of Endogenous Retinoid Signalling Determine Cessation of Body Axis Elongation

Abstract: By analyzing cellular and molecular changes in key cell populations in the tailbud during embryogenesis, this work uncovers critical signaling events that determine vertebrate body length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
184
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(203 citation statements)
references
References 79 publications
19
184
0
Order By: Relevance
“…We observed that cells in the NMP domain of the posterior wall of the tailbud adhere to each other and to the border between the epidermis and the NMP population along the apical edge of the NMPs. In a process that appears strikingly similar to that described in a recent report of mouse epiblast cells undergoing EMT to form mesoderm during gastrulation (Ramkumar et al, 2016), individual cells were observed to undergo apical constriction, ingression, and epithelial layer exit, while remaining tethered to the epithelial layer by a long apical extension of the membrane for a period of time before complete dissociation (Fig. 7A,B, Movies 1 and 2).…”
Section: High-resolution Imaging Of the Tailbud Emtsupporting
confidence: 80%
See 2 more Smart Citations
“…We observed that cells in the NMP domain of the posterior wall of the tailbud adhere to each other and to the border between the epidermis and the NMP population along the apical edge of the NMPs. In a process that appears strikingly similar to that described in a recent report of mouse epiblast cells undergoing EMT to form mesoderm during gastrulation (Ramkumar et al, 2016), individual cells were observed to undergo apical constriction, ingression, and epithelial layer exit, while remaining tethered to the epithelial layer by a long apical extension of the membrane for a period of time before complete dissociation (Fig. 7A,B, Movies 1 and 2).…”
Section: High-resolution Imaging Of the Tailbud Emtsupporting
confidence: 80%
“…1L,M). Tailbud NMPs are characterized by the co-expression of ntla and sox2 Olivera-Martinez et al, 2012). Similar to ntla, sox2 expression in the tailbud was expanded after loss of FGF signaling (Fig.…”
Section: Fgf Signaling Is Required For Pm Induction From Nmpsmentioning
confidence: 94%
See 1 more Smart Citation
“…FGF signalling is required for convergence and extension, but not posterior volumetric growth in zebrafish FGF signalling is known to be important for posterior body elongation across vertebrates (Bénazéraf et al, 2010;Bouldin et al, 2014;del Corral and Storey, 2004;Olivera-Martinez et al, 2012;Lawton et al, 2013). We applied our morphometric approach to determine whether FGF signalling plays a role in volumetric growth and/or convergence during posterior body elongation in zebrafish.…”
Section: Differential Tissue Contributions To Both Volumetric Growth mentioning
confidence: 99%
“…The physiological significance of RARγ expression in the embryonic posterior is uncertain. RARγ might function to terminate the body axis at late stages by inducing apoptosis (Olivera-Martinez et al, 2012), but that model would not explain the strong expression of RARγ observed at neurula, continuing through tailbud stages, despite the apparent absence of RA.…”
Section: Introductionmentioning
confidence: 98%